Nilai-Nilai Realitas Profetik Novel Bulan Terbelah di Langit AMERIKA dan Pengembangan - Yesi Desiana; Muhammad Fuad; Munaris Munaris (Universitas Lampung, 2017)
The problem in this research is the values of the prophetic reality in the novel of the American Hidden Moon as literary materials for MA. The aims of this study are the values of the prophetic reality contained in the novel of the Hidden Moon in the Sky of America. The approach in describing the values of prophetic reality using Kutowijoyo's prophetic literary approach. Development as a teaching material in this research use Borg and Gall's research and development. The results showed that the values of prophetic reality contained in the novel Bulan Terbelah in the American sky marked by the representation of da'wah values can be grouped into 3 classifications, namely ammar ma'ruf, nahi munkar, tu'minu billah. This research yield materials product teach art in the form of Sheet Activity Of Student (LKS). Election of good novel and according to requirement will yield study of good art also.AbstrakTujuan dalam penelitian ini adalah mendeskripsikan nilai-nilai realitas profetik pengembangan bahan ajar sastra di MA dengan sumber data novel Bulan Terbelah di Langit Amerika karya Hanum Salsabiela Rais dan Rangga Almahendra. Pendekatan dalam mendeskripsikan nilai-nilai realitas profetik menggunakan pendekatan sastra profetik Kutowijoyo. Pengembangan sebagai bahan ajar dalam penelitian ini menggunakan model pengembangan research and development Borg and Gall. Hasil penelitian novel tersebut menunjukan bahwa terdapat nilai-nilai realitas profetik yaitu ammar maruf, nahi munkar, tuminu billah. Penelitian ini menghasilkan produk bahan ajar sastra berupa Lembar Kegiatan Siswa (LKS). Pemilihan novel yang baik dan sesuai kebutuhan akan menghasilkan pembelajaran sastra yang baik pula.Kata kunci : nilai-nilai realitas profetik, novel, bahan ajar